Relationship between volition, physical activity and weight loss maintenance: Study rationale, design, methods and baseline characteristics. Issue 3 (May 2017) - Dandanell, Sune; Elbe, Anne-Marie; Pfister, Gertrud; Elsborg, Peter; W Helge, Jørn
Aims: To investigate the relationship between volition, physical activity and weight loss maintenance. Methods: We recruited 84 sedentary (maximal oxygen uptake: 25 ± 5 ml/min), overweight and obese (Body mass index (BMI) 38 ± 7 m/h 2, fat 44 ± 7 %) women ( n = 55) and men ( n = 29) for an interdisciplinary prospective study with follow-up. The change in lifestyle and weight loss is promoted via a 3-month intensive lifestyle intervention at a private health school. The intervention consists of supervised training (1–3 hours/day), a healthy hypo-caloric diet (−500 to −700 kCal/day) and education in healthy lifestyle in classes/groups. The participants' body weight and composition (Dual Energy X-ray absorptiometry), volitional skills (questionnaire), physical activity level (heart rate accelerometer/questionnaire) and maximal oxygen uptake (indirect calorimetry) are to be monitored before, after, and 3 and 12 months after the intervention. Results: At the 12-month follow-up, three different groups will be established: Clinical weight loss maintenance (> 10% weight loss from baseline), moderate weight loss maintenance (1–10% weight loss) and no weight loss (or weight regain). A linear mixed model analysis will be used to compare levels of volitional skills, physical activity and maximal oxygen uptake over time, between the three groups. Correlational analyses will be used to investigate possible associations between volition, maximal oxygen uptake, physical activity level and weight loss maintenance. Conclusions :If specific volitional skills are identified as predictors of adherence to physical activity and success in clinical weight loss maintenance, these can be trained in future intensive lifestyle interventions in order to optimize the success rate.